2008
DOI: 10.1021/ie800458h
|View full text |Cite
|
Sign up to set email alerts
|

Improved Drying in a Pulsation-Assisted Fluidized Bed

Abstract: Gas flow pulsation was employed to improve the drying of porous pharmaceutical granules in a cylindrical fluidized bed. In our approach, a fraction of the total flow was oscillating intermittently and periodically, typically at 3 Hz during 2 min and remaining constant during the other 2 min of each 4 min cycle. It was found that such pulsation-assisted fluidization not only shortened the total drying time but also enhanced homogeneity. A transition in fluidization behavior, reflected by a distinct transition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…However, this frequency is lower than the frequency after the critical moisture content which suggests the defluidized portion of the bed affects the hydrodynamics. A recent study published on pulse fluidized bed drying of the same pharmaceutical granule as that used in the present study supports this [9]. Pulsation of the fluidization gas improved the mixing in the bottom region of the cylindrical bed and also changed the hydrodynamics.…”
Section: Bubbling Frequencysupporting
confidence: 87%
See 1 more Smart Citation
“…However, this frequency is lower than the frequency after the critical moisture content which suggests the defluidized portion of the bed affects the hydrodynamics. A recent study published on pulse fluidized bed drying of the same pharmaceutical granule as that used in the present study supports this [9]. Pulsation of the fluidization gas improved the mixing in the bottom region of the cylindrical bed and also changed the hydrodynamics.…”
Section: Bubbling Frequencysupporting
confidence: 87%
“…The granule will also exhibit channelling when fluidized [1]. To improve the fluidity of cohesive powders, researchers have proposed several techniques including mechanical vibration [2][3][4][5]7], bed stirring [4,6,7] and gas pulsation [8,9]. However, the pharmaceutical industry does not employ any of these assisting techniques to aid their granule fluidity during drying.…”
Section: Introductionmentioning
confidence: 99%
“…By pulsing the gas, fluidization is more uniform, and channeling and clumping are prevented. This improves the performance of fluidized bed combustion and drying [81,82]. Periodically perturbing the gas in a fluidized bed can suppress chaos by 'phase locking ' [83], however the periodicity of the bubble pattern is remarkable [79 ].…”
Section: Dynamic Self-organizationmentioning
confidence: 99%
“…A mathematical model was proposed to offer approximate predictions of the natural frequency of the fluidized bed, around which the pulsation was most effective. DEM simulation by Wang and Rhodes [19,32] confirmed that a frequency of 3-10 Hz would be most effective in ameliorating gas-solid interaction. Periodically formed horizontal gas channels were spotted where they quickly gave rise to regular bubbles, which moved up to the surface of the bubbling bed.…”
Section: Introductionmentioning
confidence: 97%
“…Besides relying on improving the design of gas distributors and operated at high flow rates, pulsation and vibration have been commonly used in granulation, coating and drying of sticky powders and irregularly shaped agricultural products [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Pulsed fluidized beds, in which the gas flow rate oscillates periodically with time, have been proven effective in transforming random and chaotic bubble behavior into regular and ordered patterns, improving the fluidization quality of coarse particles greatly [28].…”
Section: Introductionmentioning
confidence: 99%